FIELD WORK: ETNOGRAFI DAN ETNOGRAFI DIGITAL - Mita Rosaliza; Hesti Asriwandari; Indrawati Indrawati (Universitas Lancang Kuning, 2023)
The presence of digital platforms increasingly permeates contemporary everyday culture, necessitating a re-evaluation of observational studies on social and cultural phenomena. Traditional qualitative research methods that rely on physical locations face challenges in the era of digital platforms. This article aims to explain the use of ethnography and digital ethnography in fieldwork, combining classic ethnographic methods with participant observations in locations where digital platforms are utilized. Technical exploration can uncover social and cultural assumptions embedded in interactions and interviews, as well as how their accessibility can create symbolic meanings. Meanwhile, participant observation focuses on the perspectives of digital platform users within a community. Referring to pioneering works in the field of